Students' Strategy in Describing a Product: The case of ESP Writing class - Dewi Surani; Ana Utami Fatoni (Loquen, 2020)
Describing a product is one of discussion that the students should learn to express the words that of selling. This study aims at investigating how the students’ abilities and difficulties in describing a product in the economics class of Bina Bangsa University. The respondents were students from the third semester and analyzed using descriptive-qualitative study. The result of the study depicted that students faced difficulties in both organizing and developing ideas. They were difficult to choose appropriate vocabulary and to manage the words grammatically correct in expressing the language. It suggested students need attention in learning descriptive text structures whether in developing ideas, grammar, and vocabulary chosen. They should be provided by example and practice for achieving the ability to describe a product.